Systemic Scleroderma in Childhood: A Case Report - Aslı ASLAN,; Güldane KOTUROĞLU,; Betül SÖZERİ,; Zafer KURUGÖL, (Archives of Rheumatology, 2014)
Juvenile systemic scleroderma is a rare chronic multi-system connective tissue disease in childhood. Although rare in children, it is an important cause of morbidity and mortality. Juvenile systemic scleroderma is one of the most severe rheumatologic conditions diagnosed in children. In this article, we report a six-year-old boy diagnosed with scleroderma.